2023
DOI: 10.3390/jfb14060307
|View full text |Cite
|
Sign up to set email alerts
|

Guided Bone Regeneration Using a Novel Magnesium Membrane: A Literature Review and a Report of Two Cases in Humans

Abstract: Guided bone regeneration (GBR) is a common procedure used to rebuild dimensional changes in the alveolar ridge that occur after extraction. In GBR, membranes are used to separate the bone defect from the underlying soft tissue. To overcome the shortcomings of commonly used membranes in GBR, a new resorbable magnesium membrane has been developed. A literature search was performed via MEDLINE, Scopus, Web of Science and PubMed in February 2023 for research on magnesium barrier membranes. Of the 78 records review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Wound dehiscence was previously reported in an in vivo study using the membrane [16]. However, in this instance, and in concurrence with the published cases [24][25][26][27], there were no clinical observations associated with the release of hydrogen gas.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Wound dehiscence was previously reported in an in vivo study using the membrane [16]. However, in this instance, and in concurrence with the published cases [24][25][26][27], there were no clinical observations associated with the release of hydrogen gas.…”
Section: Discussionsupporting
confidence: 85%
“…In the reported study, the membrane maintained a barrier function in a GBR model as efficiently as a collagen membrane control group [16]. The potential for the membrane has also been demonstrated clinically [24,26,27].…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The magnesium-based GBR membrane has a similar barrier function to the collagen membranes but exerts additional space maintenance properties comparable to titanium-based products [ 28 , 29 ]. It has already been shown that the membrane provides a good bone tissue regeneration and soft tissue healing in combination with an allograft biomaterial [ 33 , 34 ], and a recent review highlighted the many benefits of magnesium metal membranes. The biocompatibility, inflammatory response, and non-toxicity of the magnesium membrane were recently reported [ 28 ].…”
Section: Introductionmentioning
confidence: 99%